Respuesta :

                       Question # 9

Answer:

  • (x, y) = (5, 9)
  • (x, y) = (2, 3)
  • (x, y) = (0, -1)

The graph of [tex]y = 2x-1[/tex]  is shown and attached below.

Step-by-step explanation:

Considering the function

[tex]y = 2x-1[/tex]

Putting x = 5

[tex]y\:=\:2\left(5\right)-1[/tex]

[tex]y = 9[/tex]

(x, y) = (5, 9)

Putting x = 2

[tex]y\:=\:2\left(2\right)-1[/tex]

[tex]y = 3[/tex]

(x, y) = (2, 3)

Putting x = 0

[tex]y\:=\:2\left(0\right)-1[/tex]

[tex]y = -1[/tex]

(x, y) = (0, -1)

The graph of [tex]y = 2x-1[/tex]  is shown and attached below.

                   Question # 10

Answer:

  • (x, y) = (4, 5)
  • (x, y) = (1, -4)
  • (x, y) = (0, -7)

The graph of [tex]y = 3x-7[/tex]  is shown and attached below.

Step-by-step explanation:

Considering the function

[tex]y = 3x-7[/tex]

Putting x = 4

y = 3x - 7

y = 3(4) - 7

y = 12 - 7

y = 5

(x, y) = (4, 5)

Putting x = 1

y = 3(1) - 7

  = 3 - 7

  = -4

y = -4

(x, y) = (1, -4)

Putting x = 0

y = 3(0) - 7

  = 0 - 7

  = -7

y = -7

(x, y) = (0, -7)

The graph of [tex]y = 3x-7[/tex]  is shown and attached below.

                   Question # 11

Answer:

  • (x, y) = (4, -8)
  • (x, y) = (2, 0)
  • (x, y) = (1, 4)

The graph of y = -4x + 8 is shown and attached below.

Step-by-step explanation:

Considering the function

y = -4x + 8

Putting x = 4

y = -4x + 8

  = -4(4) + 8

  = -16 + 8

  = -8

y  = -8

(x, y) = (4, -8)

Putting x = 2

y = -4x + 8

  = -4(2) + 8

  = -8 + 8

  = 0

y = 0

(x, y) = (2, 0)

Putting x = 1

y = -4x + 8

  = -4(1) + 8

  = -4 + 8

  = 4

(x, y) = (1, 4)

The graph of y = -4x + 8 is shown and attached below.

                   Question # 12

Answer:

  • (x, y) = (7, -7)
  • (x, y) = (5, -3)
  • (x, y) = (3, 1)

The graph of y = 7 - 2x is shown and attached below.

Step-by-step explanation:

Considering the function

y = 7 - 2x

Putting x = 7

y = 7 - 2x

  = 7 - 2(7)

  = 7 - 14

  = -7

y = -7

(x, y) = (7, -7)

Putting x = 5

y = 7 - 2x

  = 7 - 2(5)

  = 7 - 10

  = -3

y = -3

(x, y) = (5, -3)

Putting x = 3

y = 7 - 2x

  = 7 - 2(3)

  = 7 - 6

  = 1

y = 1

(x, y) = (3, 1)

The graph of y = 7 - 2x is shown and attached below.

Ver imagen SaniShahbaz
Ver imagen SaniShahbaz
Ver imagen SaniShahbaz
Ver imagen SaniShahbaz
ACCESS MORE